ANALISIS IMPLEMENTASI DAN PENGEMBANGAN KURIKULUM MERDEKA PENDIDIKAN AGAMA ISLAM DI UNIVERSITAS NEGERI YOGYAKARTA - Miftahul Janah; Muh Wasith Achadi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
The purpose of this research is to determine and analyze the implementation of the Independent Curriculum as well as the development and evaluation carried out in higher education. This research uses a qualitative method with a descriptive approach which aims to describe the subject related to the conditions observed and data obtained through observation, interviews and documentation. This research was conducted at Yogyakarta State University. Data from observations, interviews and document analysis can be analyzed using content analysis to identify concepts, objectives, methods and independent curriculum evaluation and develop them using relevant theories.The findings of this research are several obstacles in implementing the Merdeka curriculum at Yogyakarta State University, namely understanding the different characteristics of students due to the still inherent passive school culture, classroom conditioning in the learning process, lack of active learning in the classroom.In this research the author analyzes the forms and patterns of problems that occur in the field and develops an independent curriculum to improve existing problems based on the substance of the curriculum as a system, where the curriculum is an inseparable unit. separated between components.